Implementing tactical plans to improve water-energy loss management - Loureiro, D. (2015)
Water utilities are aware of the water-energy loss relevance in supply systems. However, they still mainly focus on daily water loss control (real and apparent losses), without considering the impact on embedded energy. Moreover, they are mostly concerned with the economic dimension and, in most cases, tend to disregard the impact that water-energy loss may have on the quality of service, communication with the customers, social awareness, water quality and environment. This paper focuses on the application of the AWARE-P IAM methodology to improve water-energy loss management in water supply systems while demonstrating the main benefits from implementing an integrated approach for water losses and related energy assessment. Results show that indeed the participating iPerdas utilities were able to define tactical measures prone to a more efficient and sustainable service.